2017
DOI: 10.1080/21699763.2017.1302892
|View full text |Cite
|
Sign up to set email alerts
|

How does the welfare state model influence social political attitudes? An analysis of citizens' concrete and abstract attitudes toward poverty

Abstract: This study examines the relationship between the welfare state models and social political attitudes. The data are based on the sixth round of the European Social Survey. The study revealed a mechanism of how the relationship between concrete and abstract attitudes differs between the welfare states. In the Anglo-Saxon and Nordic welfare states the relationship is a positive one, which indicates that the welfare state has a broad support among citizens. In the Continental, Eastern and Southern welfare states t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 79 publications
1
15
0
Order By: Relevance
“…Previous work has shown that compared to other parts of the welfare state, citizen support for health care is much higher (Jensen, 2011(Jensen, , 2012Jensen & Petersen, 2017), potentially because of deeply rooted biological and evolutionary mechanisms triggering a willingness to help the sick in need. This is different from other areas of the welfare state, in particular unemployment insurance or social assistance, as being unemployed or in poverty might also be attributed to individuals' inaction to overcome these situations (Toikko & Rantanen, 2017;Van Oorschot, 2006).…”
Section: The Impact Of the Crisis Over Timementioning
confidence: 83%
“…Previous work has shown that compared to other parts of the welfare state, citizen support for health care is much higher (Jensen, 2011(Jensen, , 2012Jensen & Petersen, 2017), potentially because of deeply rooted biological and evolutionary mechanisms triggering a willingness to help the sick in need. This is different from other areas of the welfare state, in particular unemployment insurance or social assistance, as being unemployed or in poverty might also be attributed to individuals' inaction to overcome these situations (Toikko & Rantanen, 2017;Van Oorschot, 2006).…”
Section: The Impact Of the Crisis Over Timementioning
confidence: 83%
“…Toikko & Rantanen, 2017). However, the degree of individualism cannot be directly related to the high or low welfare state performance in social policy because, for instance, the Nordic countries seem to have a high welfare state performance but also relative high support (i.e., preferences) for the state's welfare responsibility.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Sweden is a typical example of an individualistic country (Hofstede Insights, 2018), and Sweden is also an example of a highly developed welfare system with broad universal benefits and services. In turn, Portugal is a country with a collectivistic culture (Hofstede Insights, 2018), but its social political system does not place as much emphasis on the state's responsibility as with the case of Sweden (Esping-Andersen, 2015; Roosma, Van Oorschot, & Gelissen, 2013;Toikko & Rantanen, 2017). The relationship between country-level cultural values and welfare attitudes is thus a complex issue.…”
mentioning
confidence: 99%
“…also Wacquant 2009). Studies of welfare state regimes have a relatively long history, given that their institutional origins are linked to the end of World War II (Wilensky and Lebeaux 1958;Hunter 1958;Titmuss 1974;Mishra 1981). One of the most common typologies of welfare states was proposed by the Danish sociologist Gøsta Esping-Andersen (1990).…”
Section: Social Welfare and The Welfare Statementioning
confidence: 99%